Dari JI ke ISIS: Pemikiran Strategis dan Taktis Gerakan Terorisme di Asia Tenggara - Sholeh, Badrus (Jurnal Hubungan Internasional, 2016)
This article examines the transformation of terrorist groups in the Southeast Asia, ranging from from Jama’ah Islamiyah (JI) to the Islamic State of Iraq and Syria (ISIS). It examines the movements and thoughts of the combatant leaders who fought in the battlefields and wrote books, blogging and social media to defend their jihad argument and strategically used by young generation and current terrorist groups, affiliated to JI and ISIS to recruit, consolidate and fight against so-called infidel governments of Southeast Asia and global coalition. The strategy and tactic of ISIS in the Southeast Asia vary from the networking of Syria-Iraq and Southeast Asia through Katibah Nusantara in Syria-Iraq and the home-grown terrorist networks in Indonesia, Malaysia and the Philippines. The challenge for state and civil society in Southeast Asia is greater given the current terrorist groups’ movement which mostly recruit the youth and taking advantages from the online media, blogging and social media. It challenged the security threats and counter narratives developed state and civil society. Artikel ini membahas transformasi kelompok teroris di Asia Tenggara dari Jama’ah Islamiyah (JI) ke Negara Islam Irak dan Suriah (NIIS). Artikel ini membahas gerakan dan pemikiran komandan dan tokoh kombatan yang tidak hanya terlibat dalam pertarungan tetapi juga menulis buku, blog, media sosial untuk mempertahankan argumen Jihad mereka dan secara strategis digunakan oleh generasi muda dan kelompok teroris saat ini, yang berafiliasi dengan JI dan ISIS untuk merekrut, melakukan konsolidasi dan bertarung melawan pemerintah dan koalisi global thoghut. Strategi dan taktik ISIS Asia Tenggara bekerja dalam jaringan Suriah-Irak-Asia Tenggara melalui Katibah Nusantara di Suriah dan Irak dan jaringan teroris dalam negeri di Indonesia, Malaysia dan Filipina. Tantangan negara dan masyarakat sipil di Asia Tenggara lebih besar khususnya setelah bagaimana kelompok teroris merekrut kebanyakan pada generasi muda dan mengambil manfaat besar pada media online, blog dan media sosial. Hal ini menjadi tantangan bagi ancaman keamanan dan kontra narasi yang dikembangkan oleh pemerintah dan masyarakat sipil.